2022
DOI: 10.1002/eom2.12212
|View full text |Cite
|
Sign up to set email alerts
|

Ultra‐fast, low‐cost, and green regeneration of graphite anode using flash joule heating method

Abstract: Graphite is the state-of-the-art anode material for most commercial lithiumion batteries. Currently, graphite in the spent batteries is generally directly burned, which caused not only CO 2 emission but also a waste of precious carbon resources. In this study, we regenerate graphite in lithium-ion batteries at the end of life with excellent electrochemical properties using the fast, efficient, and green Flash Joule Heating method (FJH). Through our own developed equipment, under constant pressure and air atmos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(16 citation statements)
references
References 35 publications
1
15
0
Order By: Relevance
“…[ 22 ] Recent work has shown that the rapid electrothermal method can be applied to evaporate the impurities, including the binder and SEI, especially the lithium salts LiF and Li 2 CO 3 . [ 17 ] Their results were similar to the traditional high‐temperature treatment under inert atmosphere. The evaporation of the volatile compounds, and the expansion of the graphite structures were observed, leading to ≈40 times increasing of the surface area.…”
Section: Resultssupporting
confidence: 66%
“…[ 22 ] Recent work has shown that the rapid electrothermal method can be applied to evaporate the impurities, including the binder and SEI, especially the lithium salts LiF and Li 2 CO 3 . [ 17 ] Their results were similar to the traditional high‐temperature treatment under inert atmosphere. The evaporation of the volatile compounds, and the expansion of the graphite structures were observed, leading to ≈40 times increasing of the surface area.…”
Section: Resultssupporting
confidence: 66%
“…As for the repaired LFP, the carbon residues were removed by LiNO 3 treatment (extra 1–2 wt%) and heavy liquid centrifuge separation 43 (>10 wt%), which can also be collected and recycled via other reported graphite recycling methods. 44–46 The carbon content in the final product was controlled within 5 wt%, as suggested by the TG curves in Fig. S1† (stoichiometrically, the added 8 wt% LiNO 3 can consume ∼2 wt% of zero-valent carbon in spent LFP at most).…”
Section: Resultsmentioning
confidence: 89%
“…Some studies have revealed that recovered GA could be regenerated as anode materials for energy storage devices after some retreatments. [103][104][105][106] Low-cost regeneration of GA from spent LIBs is of great significance to solve the problem of waste graphite utilization and pollution. Comparing with the fresh graphite, the directly recycled GA (with coating, SEI layer and other Impurities) exhibits lower initial discharge capacity, which are 354.2 and 298.7 mAh/g respectively.…”
Section: Regeneration Of Gamentioning
confidence: 99%
“…Some studies have revealed that recovered GA could be regenerated as anode materials for energy storage devices after some retreatments 103–106 . Low‐cost regeneration of GA from spent LIBs is of great significance to solve the problem of waste graphite utilization and pollution.…”
Section: Recycling Of Spent Gamentioning
confidence: 99%